UNES Hebat as a Cloud-Native GPS Attendance Platform and Institutional Technology Innovation for Higher Education Governance - Irfan Ananda Ismail; Sufyarma Marsidin; Dewirman Prima Putra; Muhammad Takdir (Indonesian Chemical Connections Society, 2026)
Background: Accountability structures governing personnel attendance in Indonesian higher education demand audit-compliant records. Paper-based registers in mid-tier private universities suffer from proxy signing, retroactive logs, physical record loss, and manual entry overhead. Objective: This study presents the design, longitudinal evaluation, and operational stress-testing of UNES Hebat, a zero-hardware cloud-native GPS attendance platform deployed at Universitas Ekasakti in Padang, West Sumatra, Indonesia. Methods: The system features Progressive Web Application clients, edge content delivery, managed cloud databases, and a three-layer verification engine (Haversine GPS geofencing, real-time photographic auditing, and server-authoritative temporal validation via database stored procedures). Performance was tracked across 181 operational days with 288 registered staff, followed by a five-day stress event with 849 student participants. Results: The platform processed 29,251 attendance records with a 99.92% present-status rate and zero downtime across 4,344 server-hours. During the five-day orientation event, the platform absorbed a nineteen-fold concurrent-user surge without infrastructure modifications or performance loss. Conclusion: Server-authoritative validation paired with managed cloud architecture provides a resilient, cost-effective model for university digital governance.